EFFECT OF ENVIRONMENTAL EDUCATION WORKSHOP ON THE KNOWLEDGE, ATTITUDE, AND BEHAVIOR CHANGES OF THE STUDENT OF ELEMENTARY SCHOOL -STUDY CASE IN LEBAK SILIWANGI – BANDUNG, INDONESIA - - Indriyani Rachman (Lembaga Penelitian Universitas Pasundan, 2017)
Indonesia is facing plenty of environmental issues. Stakeholders, including national government, environmental activists, international organizations, have been struggling to respond to these issues. Inclusion of environmental education in all level of school in Indonesia, green school and Adiwiyata program are some of the efforts that Indonesian government has done to address environmental issues in the country. This research focuses more on how to accelerate the improvement of knowledge, attitude and behavior/action toward the environment of the 340 students in four schools near Cikapundung River in Bandung. Questionnaires were distributed to explore knowledge, attitude and behavior/action of these students about waste management in general, namely 3R (Recycle, Reuse and Reduce), type of waste, separation of waste, usage of waste, waste bank, etc. This research showed that conducting workshops improves knowledge, attitude and behavior/action of the students who participated. There are other important aspects that make environmental education more successful, effective and efficient.